MAKNA AIR BAGI MASYARAKAT BALI - Nyoman Rema (Forum Arkeologi, 2013)
Water is a very important need which make all kinds of creatures can grow well. This research aims to know the meaning of water for Balinese people. The data was analysed and interpreted by using the theory of symbol. The data were collected through library research and observation method. The data was analized by comparing it with symbols which related to water. The result of this research are Visnu statuette and cupu Amerta which are compared with kala, makara and water molecule with exagonal shape. It could be concluded that water has the meaning of fertility, healing, holiness, immortality, cycle, prosperity, and conservation.Air merupakan kebutuhan yang sangat penting, menjadikan segala jenis mahluk dapat tumbuh dengan baik. Penelitian ini bertujuan untuk mengetahui makna air bagi masyarakat Bali, yang akan dianalisis dan ditafsirkan menggunakan teori simbol. Metode yang digunakan dalam penelitian ini adalah studi pustaka, observasi dan komparatif terhadap simbol-simbol yang berkaitan dengan air. Hasil dalam penelitian ini berupa, arca Dewa Wisnu, cupu amerta dikomparasi dengan kala, makara, eksagonal air. Dari hasil penelitian ini dapat disimpulkan bahwa air bermakna kesuburan, penyembuhan, penyucian, keabadian, siklus, kesejahteraan dan pelestarian.